THE ROLE OF INTERDISCIPLINARY RELATIONS IN THE PROCESS STUDYING A FOREIGN LANGUAGE IN HIGHER EDUCATION (Педагогіка вищої та середньої школи, 2007)
The article deals with application of inter-subject relations in the process of foreign language teaching with the aim of enrichment of the content of education.